SAT0496 Incidence, cardiovascular events and mortality of adult inflammatory myopathies in south korea: a nationwide population-based study. (12th June 2018) - Jung, K.H.; Kim, H.J.; Park, W.; Kwon, S.R.; Ahn, H.S.
Abstract : Background: The inflammatory myopathies (IMs), including dermatomyositis (DM) and polymyositis (PM), are rare autoimmune diseases characterised by progressive proximal muscle weakness, elevated muscle enzyme and various organ involvement. Studies on epidemiology and mortality of IMs at the national level are rare. Objectives: We conducted a nationwide population study of incidence, cardiovascular events (especially acute myocardial infarction, ischaemic stroke, haemorrhagic stroke) and survival of IMs in South Korea over the course of 11 years. Methods: We used data from the Rare Intractable Disease (RID) registry and Health Insurance Review and Assessment (HIRA) service, which include information on all IMs patients diagnosed based on uniform criteria between 2005 and 2015. Survival data from Statistics Korea linked to HIRA-RID database were used in our survival analysis. Results: In this study, total incident cases between 2005 and 2015 were 3014 (1, 860 DM patients, 1, 154 PM patients) and the mean annual incidence rate was 7.16/10 6 /year (DM was 4.42/10 6 /year, PM was 2.74/10 6 /year). The female to male ratio of DM was 2.2:1 and that of PM was 1.9:1. Cardiovascular events occurred in 155 patients during the study period. Of the patients with DM, 25 were diagnosed with AMI (SIR 1.3, 95% CI 0.9–1.9), 39 with ischaemic stroke (SIR 1.4, 95% CI 1.0–1.9), 18 with haemorrhagic stroke (SIR 1.3, 95% CI 0.8–2.0). The results of PM were similar with those of DM. Of 155 patients, 63 (40.6%) died and had a high mortality rate. 640 of 3014 patients with IMs died during the study period; 290 and 350 were male and female, respectively. The survival curve for IMs is shown in Fig.1. The DM patients showed a 5 year survival rate (YSR) of 76.8%, and a 10-YSR of 68.9%, and the PM patients showed a 5-YSR of 79.3% and a 10-YSR of 68.3%. Conclusions: This is the first study of incidence and mortality of IMs over 3000 cases by the national registry in South Korea. In this nationwide population-based study of IMs, we found still high mortality and low survival and increased cardiovascular events related mortality compared than general population. Disclosure of Interest: None declared